The survival of childhood leukemia: An 8‐year single‐center experience - Mohammadreza Bordbar; Nazila Jam; Mehran Karimi; Mahdi Shahriari; Soheila Zareifar; Omid Reza Zekavat; Sezaneh Haghpanah; Hadi Mottaghipisheh (Cancer Reports, 2023)
Abstract Background The survival of childhood leukemia has improved. We aimed to report the survival rate and the associated factors in children with acute leukemia during an 8‐year follow‐up. Aims This study investigates the 8‐year survival rates of children with acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) in Shiraz, the largest oncology center in Southern Iran. We also aimed to assess the independent factors associated with higher mortality in childhood leukemia. Methods Children 0–18 years with acute leukemia were followed from 2013 to 2021 in Shiraz, Iran. The 8‐year overall survival (OS) and event‐free survival (EFS) rates were estimated by the Kaplan–Meier method. Independent factors associated with survival were assessed by the Cox regression hazard modeling. Results We included 786 children, with 43.5% female, and a mean age of 6.32 ± 4.62 years. Patients with AML compared to ALL experienced more relapse (34.6% vs. 22.5%, p = .01) and death (31.7% vs. 11.3%, p < .001). The cumulative 8‐year OS and EFS were 81% (95% confidence interval (CI), 74.3% to 86.1%) and 68.3% (95% CI, 63.5% to 72.7%) in ALL patients and 63.5% (95% CI, 52.1% to 72.9%) and 43% (95% CI, 33.1% to 52.6%) in AML patients. Multivariable analysis revealed that hepatomegaly (hazard ratio = 4, 95% CI, 1.0 to 22.3, p = .05) was the main independent risk factor of death in ALL patients. No definite risk factor was defined for AML patients. Conclusion The survival of childhood leukemia has recently increased dramatically in low‐middle income countries. Hepatomegaly was introduced as a potential risk factor for lower survival in ALL patients. Further multicenter studies are needed to confirm the validity of this association.